In vitro regeneration and acclimatization protocols of selected ornamental plants (agapanthus praecox, justicia betonica and celosia cristata) - Jamilah Syafawati Yaacob; Azani Saleh; Hashimah Elias; Sakinah Abdullah; Noraini Mahmad; Normadiha Mohamed (Universiti Kebangsaan Malaysia, 2014)
This paper discussed on the effectiveness of BAP and NAA growth hormones on establishment of plant regeneration for selected ornamentals; Agapanthus praecox, Justicia betonica and Celosia cristata. Various explants (leaf, stem, shoot tip and bulb) derived from one-month-old aseptic seedlings of A. praecox and C. cristata, as well as explants from intact plants of J. betonica were utilized to achieve complete plant regeneration of these species. MS medium supplemented with various hormones, with an emphasis on BAP and NAA was tested to obtain direct and indirect regeneration. Both A. praecox (bulbs) and C. cristata (shoots) formed complete plantlets on MS added with 0.5-2.0 mg/L BAP and NAA, while direct regeneration was achieved for J. betonica on MS media containing BAP. Several methods were attempted to acclimatize the regenerants, with A. praecox gave the highest percentage of survival rates (96.67%), followed by J. betonica (80.00%) and C. cristata (75.00%).